2021
DOI: 10.29271/jcpsp.2021.01.65
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Success of Semi-rigid Ureterorenoscopy in Proximal Ureter Stone Treatment

Abstract: Objective: To evaluate the factors affecting the success of semi-rigid ureteroscopy in proximal ureter stones. Study Design: Descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Therefore, new techniques are needed to understand preoperative (pre-op) impacted stone formation. [2][3][4] Studies have been reported to predict the success of ESWL and spontaneous stone passage by measuring the wall thickness of the ureter where the stone is shown by computed tomography. 5,6 In this study, we aimed to study the effect of the maximum wall thickness in the stone region, and the average wall thickness on the success of URS.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new techniques are needed to understand preoperative (pre-op) impacted stone formation. [2][3][4] Studies have been reported to predict the success of ESWL and spontaneous stone passage by measuring the wall thickness of the ureter where the stone is shown by computed tomography. 5,6 In this study, we aimed to study the effect of the maximum wall thickness in the stone region, and the average wall thickness on the success of URS.…”
Section: Introductionmentioning
confidence: 99%